2017
DOI: 10.1097/tp.0000000000001755
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Clinical Trial Comparing Belatacept With Tacrolimus After De Novo Kidney Transplantation

Abstract: Belatacept-based immunosuppressive therapy resulted in higher and more severe acute rejection compared with tacrolimus-based therapy. This trial did not identify cellular biomarkers predictive of rejection. In addition, the CD28-CD80/86 costimulatory pathway appeared to be sufficiently blocked by belatacept and did not predict rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 49 publications
(60 reference statements)
2
68
1
Order By: Relevance
“…Belatacept-based immunosuppression may result in improved long-term patient and graft survival but it is less effective than Tac in preventing acute rejection [11,12]. It thus remains to be seen whether belatacept will replace Tac as the first-line immunosuppressive drug anytime soon [13][14][15]. Multicenter, randomized clinical studies also showed higher incidences of acute rejection and dnDSA development in the Tac withdrawal or rapamycin-based groups compared with Tac-based regimen [1,3,16,17] In the foreseeable future, no other novel immunosuppressants are likely to emerge that can replace Tac.…”
Section: Introductionmentioning
confidence: 99%
“…Belatacept-based immunosuppression may result in improved long-term patient and graft survival but it is less effective than Tac in preventing acute rejection [11,12]. It thus remains to be seen whether belatacept will replace Tac as the first-line immunosuppressive drug anytime soon [13][14][15]. Multicenter, randomized clinical studies also showed higher incidences of acute rejection and dnDSA development in the Tac withdrawal or rapamycin-based groups compared with Tac-based regimen [1,3,16,17] In the foreseeable future, no other novel immunosuppressants are likely to emerge that can replace Tac.…”
Section: Introductionmentioning
confidence: 99%
“…However, these findings were not confirmed in recent randomized controlled clinical trials in which belataceptbased immunosuppressive therapy was compared with tacrolimus-based immunosuppressive therapy [21][22][23]. In the study by de Graav et al [23], no association between rejection and higher frequencies of CD4 1 CD57 1 PD-1was found. In the study by de Graav et al [23], no association between rejection and higher frequencies of CD4 1 CD57 1 PD-1was found.…”
Section: Introductionmentioning
confidence: 89%
“…All former and current cross-match cytotoxicity tests were negative prior to transplantation. [Colour figure can be viewed at wileyonlinelibrary.com] institutional review board of Erasmus MC (METC number 2012-421) [23]. The study was performed according to good clinical practice (GCP) guidelines and the declaration of Istanbul [27].…”
Section: Patients and Study Designmentioning
confidence: 99%
See 2 more Smart Citations